2010
DOI: 10.1063/1.3482938
|View full text |Cite
|
Sign up to set email alerts
|

White light emission from amorphous silicon oxycarbide (a-SiCxOy) thin films: Role of composition and postdeposition annealing

Abstract: The effects of carbon and postdeposition annealing on white luminescence are studied in amorphous silicon oxycarbide (a-SiCxOy) films grown by chemical vapor deposition. The films showed strong room-temperature luminescence in a broad spectral range from blue-violet to near infrared, depending on excitation energy. Photoluminescence (PL) intensity exhibited good correlation with SiOC bond concentration. At low C (<5%), matrix PL was completely quenched after annealing in O2 even at 500 °C. PL was unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 12 publications
5
66
0
Order By: Relevance
“…As in the case of the oxide luminescence centers mentioned above, the density of both EPR detected centers is expected to diminish, and their respective luminescence, if it were to exist in the SiC x O y samples, would be quenched following prolonged oxidation or hydrogen passivation. 5,16,17 This expectation did not actually materialize in the SiC x O y samples. 5 Another potential mechanism responsible for strong luminescence from C-rich materials could be small sp 2 -carbon clusters.…”
Section: (B)mentioning
confidence: 94%
See 2 more Smart Citations
“…As in the case of the oxide luminescence centers mentioned above, the density of both EPR detected centers is expected to diminish, and their respective luminescence, if it were to exist in the SiC x O y samples, would be quenched following prolonged oxidation or hydrogen passivation. 5,16,17 This expectation did not actually materialize in the SiC x O y samples. 5 Another potential mechanism responsible for strong luminescence from C-rich materials could be small sp 2 -carbon clusters.…”
Section: (B)mentioning
confidence: 94%
“…5,16,17 This expectation did not actually materialize in the SiC x O y samples. 5 Another potential mechanism responsible for strong luminescence from C-rich materials could be small sp 2 -carbon clusters. 18 Previous FTIR studies showed the absence of C¼C bonds at $1644 cm À1 , which would result from the sp 2 -carbon molecular orbitals.…”
Section: (B)mentioning
confidence: 94%
See 1 more Smart Citation
“…Various kinds of Si−O−C ceramics were synthesized by various methods, and many mechanisms have been proposed to explain the observed PL bands. [3][4][5][6][7][8][9] Their simple chemical composition with no special activator was promising for their use in LED systems, devices of radiation detectors or environmental resistant inorganic pigments with fluorescent colors.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%
“…Gallis et al proposed the idea of C-ODC (carbon modified oxygen deficiency related centers) to explain broad PL spectra of near-stoichiometric Si−O−C films. 8 Detailed discussion of the modified ODC (II) structure is, however, very difficult.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%